Investigation of the effect of exposure to non cytotoxic amounts of microcystins - Birungi, Grace; Fong Yau Li, Sam (Metabolomics, 2011)
This paper describes a metabolomic approach for investigation of the potential effect of exposure of humans to low amounts of microcystins using HepG2 cell line. Microcystins are hepatotoxins produced by cyanobacteria (blue-green algae) which occur in water bodies with high eutrophication especially those with a slow flow rate or those that are stagnant in warm climates. Mammalian exposure to these compounds has been associated with deleterious effects and in high dosage cases, deaths of animals has been reported. The metabolic profile of HepG2 cells is closely related to that of hepatocytes and therefore serves as a good model due to their human origin. Proton nuclear magnetic resonance spectroscopy (1H NMR) and direct injection mass spectrometry (DIMS) were used to analyse media extracts from the cells and data obtained was reduced by chemometric methods. The use of principal component analysis (PCA) enabled achievement of a visual distinction between the metabolic profiles of samples exposed to microcystins, control samples (unexposed), and those which were exposed to acetaminophen (positive control). A profile of media components showed that some components in the samples exposed to microcystins increased compared to those in control samples. They included amino acids, organic acids, lipids, some purines and pyrimidines. In general exposure to low concentration of microcystin was found to interfere with amino acid metabolism, carbohydrate metabolism, lipid metabolism and nucleic acids metabolism. Furthermore, low concentration of microcystins did not result in significant cell death; rather the cells continued to proliferate.
Keywords: Metabolomics; Chronic exposure to microcystins; HepG2; 1H NMR; Direct injection MS (DIMS)